Strategi Penerapan Konsep Green City di Kota Makassar - Jihan Jamaluddin; Ananto Yudono; Arifuddin Akil (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
Indonesia is currently focusing on handling urban areas that are very vulnerable to the effects of climate change. Therefore, the implementation of integrated spatial planning is an important element in creating a comfortable, productive and sustainable city. The City of Makassar has grown into a Metropolitan City with a population around 1.4 million people. Urban problems faced by The City of Makassar include, lack of Green Open Space (GOS), increasing amount of waste, congestion, flooding, management of wastewater that has not reached 100%, PDAM pipeline leakage is still very high and community participation in handling the environment is not optimal . This study aims to determine the existing conditions based on the Asian Green City Index (AGCI) in Makassar City, analyze the level of performance of Makassar City towards the Asian Green City Index (AGCI), and develop strategies to improve the Asian Green City Index (AGCI) in Makassar City. This study uses a qualitative and quantitative approach to assess the performance of Makassar City on the six attributes of the eight Green City attributes, which are, land use and building, transportation, water, waste, sanitation, and environmental governance. The results of this study are strategies for improving performance of each of the indicators of the Asian Green City Index (AGCI), which are based on priority scales in the form of additional open green space, the application of vertical building, and so on.